83 Preclinical Evaluation of LNK001: Stringent AND-Gate Fidelity and Potent Efficacy of a Dual-Antigen CAIX/ENPP3 CAR T Cell Therapy for Clear Cell Renal Cell Carcinoma - Mark Wallet; Rebecca Larson; Yogin Patel; Janette Sutton; Bryan Smith; Colin Farrell; Angeles Estelles; Zeynep Wheeler; Kazuteru Hasegawa; Benjamin Bauer; Jakob McBroome; Diego Vargas-Inchaustegui; et al. (The Oncologist, 2026)
Abstract Background Chimeric antigen receptor (CAR) T cell therapies have transformed treatment of hematologic malignancies but have struggled to achieve safe and effective outcomes in solid tumors. On-target off-tumor (OTOT) toxicity has historically limited single-antigen approaches in clear cell renal cell carcinoma (ccRCC), where promising targets such as CAIX are also expressed on critical normal tissues. To overcome this, we developed the Logic-gated INtracellular networK (LINK) platform, a Boolean AND-gate architecture in which two synthetic receptors are coupled to distinct proximal T cell signaling adapters: the anti-CAIX domain is fused to a SLP76-based receptor and the anti-ENPP3 domain is fused to a LAT-based receptor. Productive T cell activation and cytolytic activity require co-engagement of both receptors on the same target cell, thereby restricting LNK001 activity to CAIX+ ENPP3+ dual-antigen-positive cells. Both receptors are encoded on a single bicistronic mRNA delivered by a gamma retroviral vector, enabling co-expression of both AND-gate components in each transduced T cell. LNK001 is the first clinical candidate from the LINK platform. Methods The CAIX/ENPP3 target pair was selected through an in silico analysis of over 28 million target combinations across a curated single-cell transcriptomic dataset spanning 29 million normal human cells and 390,000 malignant ccRCC cells. Co-expression at the protein level was characterized by IHC across 419 ccRCC cases spanning all disease stages and by flow cytometry on freshly resected ccRCC specimens. AND-gate fidelity was interrogated in vitro using engineered cell lines presenting CAIX and ENPP3 in dual-positive, single-positive, or antigen-negative configurations. LNK001 was assessed for cytolysis, cytokine secretion (IFNγ, IL-2, TNFα, granzyme B), and proliferation across a range of effector-to-target ratios and antigen densities. Two additional fidelity assays were employed: simultaneous co-culture with separate populations of CAIX single-positive and ENPP3 single-positive cells to model in trans antigen encounters at the interface of adjacent normal tissues, and sequential exposure to single-positive cells of one antigen followed by the other to assess priming potential. Conventional second-generation CD3-based CAR T cells targeting either CAIX or ENPP3 alone were tested in parallel as comparators. In vivo efficacy was evaluated in established CAIX+ ENPP3+ ccRCC xenograft models following a single intravenous dose of LNK001 across multiple dose levels. To model the in vivo setting in which CAR T cells encounter both malignant (dual-positive) tissue and normal (single-positive) tissue in the same animal, dual tumor models were established bearing a CAIX+ ENPP3+ tumor alongside either a CAIX+ ENPP3- or CAIX- ENPP3+ tumor as an avatar for single-antigen normal tissue. Results IHC evaluation indicated that the CAIX/ENPP3 target pair is broadly applicable, with approximately 90% of ccRCC patients expected to meet enrollment criteria and 98% of enrolled to exhibit high co-expression of both antigens. LNK001 demonstrated potent cytolysis, cytokine secretion, and proliferation only against dual-positive targets, while remaining unresponsive to single-positive cells across all conditions tested. Critically, simultaneous co-culture with separate single-positive populations elicited no cytolysis, cytokine secretion, or proliferation, confirming strict cis-restriction of the AND-gate. Sequential exposure produced no priming or sensitization, and no augmented response upon subsequent encounter with single-positive cells, indicating that transient single-antigen engagement does not lower the activation threshold of the AND-gate. In contrast, conventional second-generation CAR T cells targeting either CAIX or ENPP3 alone displayed robust activity against the corresponding single-positive cells, validating the assays and underscoring the unique fidelity of LNK001. In vivo, a single intravenous dose of LNK001 produced deep and durable tumor control of CAIX+ ENPP3+ tumors with clear dose-dependence. In dual tumor models, LNK001 showed activity exclusively against the double-positive tumors, confirming in vivo fidelity of the AND-gate. Conclusions LNK001 combines stringent dual-antigen fidelity with potent and durable in vivo activity against dual-positive ccRCC tumors. Together, these findings provide a strong preclinical foundation for the upcoming Phase 1 clinical trial of LNK001 in patients with advanced and metastatic ccRCC.